The Potent of Aspergillus parasiticus to Produce Aflatoxin B1 on the Maize Flour During Storage - Agus Selamat Duniaji; Made Indri Hapsari Arihantana; Ni Nyoman Puspawati (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2016)
Aflatoxin B1 contamination caused by Aspergillus parasiticus and Aspergiluus Aspergillus flavus is a great concern in maize production worldwide. A. parasiticus infection and aflatoxin B1 contamination are usually found in maize and their processed during storage, distribution and processing. Aflatoxin B1 contamination in food and feed can cause the cancer diseases in animal and human. This research was aimed to determinate the potency of A. parasiticus to produce aflatoxin B1 in maize during storage 0, 5, 10 and 15 days. The research methods was using Completed Random Design (CRD) with three replicated. The research was investigation of a number of colony A. parasiticus in Petato Dextro Agar (PDA) and Aflatoxin B1 content by using Enzym Linked Immunosorbant Assay (ELISA). Result of research showed that A.parasiticus were susceptible to grow in maize flour and produce aflatoxin B1 during storage. The population of A. parasiticus in maize flour were 9.5 x 105 d in primary storage (0 days) that was the total colony were increasing .7 x 106 (storage 5 days), 2.5 x 107 (storage 10 days) and 1.5 x 108 cfu/g with storage 15 days A. parasiticus was a potent to produce aflatoxin B1 in myzena flour with total of aflatoxin B1 is 66.50 ppb of mayzena flour during storage 5 days , 46.40 ppb with 10 days storage, 57.00 ppb during storage 15 days and was not found in 0 days.